Biodegradability of conventional plastics : opportunities, challenges, and misconceptions - Sarkar, Anjana; Sharma, Bhasha; Shekhar, Shashank (Elsevier, 2023)
Biodegradability of Conventional Plastics: Opportunities, Challenges, and Misconceptions brings together innovative research on the biodegradability of conventional plastics, providing an extensive overview of approaches and strategies that may be implemented, while also highlighting other methods for alleviating the eventual environmental impact of plastics. The book begins by providing a lifecycle assessment of plastics, the environmental impact of plastic waste, and the factors that affect the biodegradability of plastics. The different categories and terminologies surrounding bio-based plastics and biodegradable plastics are then defined and explained in detail, as are the issues surrounding bioplastics. Other sections discuss biodegradability, approaches for enhanced biodegradability of various major types of plastics, including polyolefins, polyethylene terephthalate (PET), polystyrene, poly(vinyl chloride), automotive plastics and composites, and agricultural plastic waste. The final part of the book focuses on further techniques and emerging areas, including the utilization of chemical additives, nanomaterials, the role of microbes in terms of microbial degradation and microbial attaching, revalorization of plastic waste through industrial biotechnology, and future opportunities and challenges.